Experimental evaluation of cement mortars with recycled brass fibres from the electrical discharge machining process. (20th June 2020) - Borinaga-Treviño, R.; Orbe, A.; Canales, J.; Norambuena-Contreras, J.
Highlights: Recycled brass fibres from electrical discharge machining were used in mortars. Mortars with machined fibres were similar to those with not-machined fibres. Fibres did not alter mortar consistency but increased its thermal conductivity. Fibres were too short to improve mechanical properties of the mortar. Abstract: This paper aims to evaluate the effect of recycled brass fibres on the physical, thermal and mechanical properties of cementitious mortars. For that purpose, seven different mortars, with the same water/cement ratio but using two different brass fibres were manufactured. Not-machined brass fibres were used as a reference and compared to the waste brass fibres obtained as a by-product of wire cutting methods through electrical discharge machines. Both fibres were added to the mortars in proportions of 0.25%, 0.5% and 1% by volume of mortar. The morphology and presence of elements in the fibres were evaluated by scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy (EDX). In addition, ultrasonic pulse velocity and thermal conductivity were measured to evaluate the mortar quality and the fibre dispersion into the mortar specimens. Mechanical properties were studied through flexural and compression tests. Since the fibres present a reduced length, the effect on both porosity and bulk density is negligible and the reduction on ultrasonic pulse velocity and compression strength and the slight increment on flexural strength is not remarkable due to the limited anchorage provided. Nonetheless, the improvement in the thermal conductivity of the developed mortars with recycled brass fibres, supports focusing on the niche market of heating installations, such as underfloor heating or closed-loop geothermal heat exchangers.